PERAN BEBERAPA BAHAN SILIKAT (Si) DAN PUPUK FOSFAT (P) DALAM MEMPERBAIKI SIFAT KIMIA TANAH ANDISOL DAN PERTUMBUHAN TANAMAN - Cici Chairunnisa; Hamidah Hanum; Mukhlis Mukhlis (Universitas Sumatera Utara, 2013)
The objective of this research was study the role of silicate material and phosphat fertilizer inimproving soil chemical charachteristics and plant growth. Andisols material was taken fromagriculture area with horticulture commodity in Kuta Rakyat Village, Naman Teran Subdistrict,Karo Regency. This research used factorial blocky randomized design with 3 block and 2 factors.The silicate material were consisted of four kind are : B0 (control), B1 (Agrosil), B2 (coarse grass),B3 (straw rice). The treatment of phosphate fertilizer consisted of four levels, namely : F0 (0 ppm P),F1 (100 ppm P), F2 (200 ppm P), and F3 (300 ppm P). Silicate material was incubated for 45 daysand then applied P fertilizer. The plant kept until vegatative phase in green house. The result of thisresearch showed that the affect of material silicate of coarse grass was very good in increasing Puptake,diameter of stem, dry weight root,dry weight crown, and height plant. And then straw rice isvery good in decrease P retention and Agrosil is very good in increase SiO2 available. The effect ofP fertilizer is not significant while the effect of interaction of silicate material and P fertilizer onlysignificant in hight plant.Keywords : Andisols, silicate material, and phosphate